2020
DOI: 10.1155/2020/3952175
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for DOA and Time Delay Joint Estimation in Multipath OFDM Environment

Abstract: Joint time delay and direction of arrival estimation based on uniform linear arrays in Orthogonal Frequency Division Multiplexing (OFDM) systems has to face the problems posed by coherent multipath environments and high computational complexity. In this paper, a novel fast method is proposed to achieve a joint direction-of-arrival (DOA) and time-dealy (TD) estimation of multipath OFDM signals by fully using space-frequency characteristics. Firstly, we construct an extended virtual array by combining the array … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Li et al [17] introduced a new approach for exploiting space-frequency features to estimate DOAs (Direction-of-Arrivals) and TDEs of multi-path OFDM (Orthogonal Frequency Division Multiplexing) signals. The study's scheme combined array structures and frequencies to generate extended virtual arrays.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al [17] introduced a new approach for exploiting space-frequency features to estimate DOAs (Direction-of-Arrivals) and TDEs of multi-path OFDM (Orthogonal Frequency Division Multiplexing) signals. The study's scheme combined array structures and frequencies to generate extended virtual arrays.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A population agent using a typical Kalman filter framework to solve optimization issues comprised simulated measurement procedures [ 26 ]. Their findings from SKF were compared with other metaheuristic algorithms using statistical analysis where findings revealed that the suggested SKF algorithm was a promising technique that outperformed various well-known metaheuristic algorithms such as GAs (Genetic Algorithms), PSOs (Particle Swarm Optimizations), BHAs (Black Hole Algorithms), and GWOs (Grey Wolf Optimizers) [ 27 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…(iv) Compared with the existing RIS-and OFDM-based localization algorithms [23,24], the proposed algorithm can obtain the required parameters for localization based on a single station node in a coherent environment. Simulation results show that the proposed algorithm avoids the aperture loss of current smoothing algorithms [22,25] when processing coherent signals and thus has more advantages in terms of estimation accuracy.…”
Section: Introductionmentioning
confidence: 99%